2015
DOI: 10.1103/physreve.91.030501
|View full text |Cite
|
Sign up to set email alerts
|

Topological defect transformation and structural transition of two-dimensional colloidal crystals across the nematic to smectic-Aphase transition

Abstract: We observe that topological defects in nematic colloids are strongly influenced by the elasticity and onset of smectic layering across the nematic (N) to smectic-A (SmA) phase transition. When approaching the SmA phase from above, the nematic hyperbolic hedgehog defect that accompanies a spherical colloidal inclusion is transformed into a focal conic line in the SmA phase. This phase transformation has a strong influence on the pairwise colloidal interaction and is responsible for a structural transition of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
5
20
1
Order By: Relevance
“…The reshaping of the boojum defect is somewhat similar to that observed in case of hyperbolic hedgehog defect in dipolar colloids across the N-SmA transition. 29 In the latter case, using Landau-de Gennes Q-tensor modeling (in the N phase), we showed that the increase of bend elastic constant (K 33 ) replaces the energetically costly bend distortion by more favorable splay distortion, concentrated in an elongated tail. However, one important difference is that, in case of dipolar colloid, the point defect moves toward the surface of the particle just before the transition, whereas in case of boojum defect similar movement is not observed.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…The reshaping of the boojum defect is somewhat similar to that observed in case of hyperbolic hedgehog defect in dipolar colloids across the N-SmA transition. 29 In the latter case, using Landau-de Gennes Q-tensor modeling (in the N phase), we showed that the increase of bend elastic constant (K 33 ) replaces the energetically costly bend distortion by more favorable splay distortion, concentrated in an elongated tail. However, one important difference is that, in case of dipolar colloid, the point defect moves toward the surface of the particle just before the transition, whereas in case of boojum defect similar movement is not observed.…”
mentioning
confidence: 81%
“…The phase transition of liquid crystal has a strong influence on the pairwise colloidal interaction. 29 In this letter, we report on the temperature dependence of equilibrium separation of a pair of isolated nematic boojum colloids. We show that the interparticle separation is linearly proportional to the orientation angle with respect to the rubbing direction and is the direct verification of the recent prediction of computer simulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In aqueous suspensions, the colloidal interaction is mostly driven by entropic or electrostatic forces, which are short‐range and isotropic, thus limiting the diversity in the resulting colloidal structures. Colloidal dispersions in nematic liquid crystals (NLCs) are very promising as they induce variety of topological defects and interact via long‐range elastic forces of the medium . They are especially interesting because the interaction is anisotropic and shape dependent, thereby providing a route to targeted colloidal assemblies .…”
Section: Introductionmentioning
confidence: 99%
“…Thus defects in liquid crystals are undesirable in any practical application of liquid crystals although they are very important and interesting from the standpoint of fundamental physics. Apart from their spontaneous creation during a phase transition, these defects can also be harvested and manipulated in a controlled manner by dispersing foreign micro particles in the liquid crystals [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%